Revisiting the racemization mechanism of helicenes. Issue 2 (8th December 2017) - Barroso, Jorge; Cabellos, Jose Luis; Pan, Sudip; Murillo, Fernando; Zarate, Ximena; Fernandez-Herrera, Maria A.; Merino, Gabriel
Abstract : Herein we propose a general mechanism for the racemization of [ n ]helicenes up to n = 24. Abstract : Herein we propose a general mechanism for the racemization of [ n ]helicenes up to n = 24. It is a concerted process for n = 4–7, but a multi-step mechanism is followed for n ≥ 8, involving 2 n − 14 intermediates. The changes in the barriers are a delicate consequence of the steric hindrance and the π-interactions.